2018
DOI: 10.1002/msc.1232
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of a patient‐initiated self‐monitoring service in inflammatory arthritis: A qualitative exploration

Abstract: Overall, participants were positive about the new service, in comparison with usual care, valuing its tailored approach and empowering effects. Further work is needed to ensure adherence to the service protocol and address anxieties around self-monitoring prior to any widespread implementation of the service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Due to this lack of professional staff, patients are facing substential diagnostic delays, often causing irreversible damage [26]. In line with other reports, current care was reported to be inefficient and burdensome [27,28].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Due to this lack of professional staff, patients are facing substential diagnostic delays, often causing irreversible damage [26]. In line with other reports, current care was reported to be inefficient and burdensome [27,28].…”
Section: Discussionmentioning
confidence: 81%
“…Improving this access to HCP feedback should be a main goal of a new care model approach. Prior studies reported on the benefit of guidebooks [29] and an initial structured training with checklists to inform when to contact the rheumatology team [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, traditional physician-driven monitoring strategies may lead to patients repeatedly presenting for routine outpatient follow-up when they are feeling well and specialist review is unlikely to result in clinical actions. Both patients and clinicians may find such visits unnecessary or inefficient 17–19. Finally, despite well-recognised benefits in terms of patient-centredness, the implementation and impact of routine registration of PROMs are limited by a lack of integrated instruments, non-disease-specific tools and time constraints 20–22…”
Section: Introductionmentioning
confidence: 99%
“…These patients are scheduled for regular follow-up visits in specialist health care, which can be time-consuming, especially for those active in the workforce. Patients have also reported that in this mode of regular follow-up the health care professionals (HPs) only see a narrow timeframe of their disease course, with important changes often taking place between visits [ 1 ].…”
Section: Introductionmentioning
confidence: 99%